2013
DOI: 10.9721/kjfst.2013.45.6.721
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Antioxidant Activity of Yogurt Added with Whole Barley Floura

Abstract: In this study, a yogurt containing skim milk powder and whole barley flour was fermented with lactic acid bacteria, and its quality and properties were estimated. The yogurts with 1% and 3% barley flour had lower pH values, higher titratable acidity, and higher Brix values than the control. In addition, the viable cell counts were lower and viscosity was higher. The value of L was low, and the values of a and b were high. The yogurt with 3% barley flour had more lactic acid than the control and showed a substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
4
0
0
1
Order By: Relevance
“…There was a significant increase (at 5% significance) for yogurt's total antioxidant activity attribute with barley flour derived from R&G grains at all levels compared with the control sample. These findings are in line with those reported by Lee et al (2013), Lee et al (2015), Ismail et al (2018), and Lee et al (2022).…”
Section: Physiochemical Analysissupporting
confidence: 93%
See 3 more Smart Citations
“…There was a significant increase (at 5% significance) for yogurt's total antioxidant activity attribute with barley flour derived from R&G grains at all levels compared with the control sample. These findings are in line with those reported by Lee et al (2013), Lee et al (2015), Ismail et al (2018), and Lee et al (2022).…”
Section: Physiochemical Analysissupporting
confidence: 93%
“…The more you add it, the clearer it becomes. The findings obtained agree well with those previously reported by Lee et al (2013); Lee et al (2022). In this regard, Lee and Lee (2014) reported that adding barley flour decreased the lightness of yogurt.…”
Section: Physiochemical Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…증진 효과가 있는 식품이다. 이처럼 발효유는 건강증진기 능성을 갖는 기호성 식품으로써 메밀 (8), 마늘 (9), 오가피 (10), 유자 (11), 산수유 (12), 함초(13), 통보릿가루 (14) 등의 기능성 식품들을 첨가하여 기존 발효유보다 기능성을 강화 시키고 항산화활성을 높이는 새로운 형태의 발효유 개발을 위한 연구가 진행되고 있다. 차(Camellia sinensis)는 동백나무과(Theaeceae)에 속하 는 상록활엽수로 열대지방에서 온대지방까지 광범위한 지 역에서 자라고 있다 (15).…”
unclassified